2018
DOI: 10.1007/s12144-018-0043-0
|View full text |Cite
|
Sign up to set email alerts
|

Two levels of personality: Temperament and values and their effects on hedonic and eudaimonic well-being

Abstract: According to McAdams and Pals, American Psychologist, 61(3), 204-217 (2006), personality is not only expressed through traits but also through characteristic adaptations, including values. In the present study we analyze how two aspects of personalitytemperament traits (Strelau 2008) and values (Schwartz 2007)-are related to hedonic and eudaimonic well-being. Earlier studies showed that temperament is linked to hedonic well-being, but the links between values and hedonic well-being are unclear. There is only l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 40 publications
5
11
0
3
Order By: Relevance
“…Our first hypothesis stated that some values would be related to well-being but also that these links will be moderated by group (supervised vs. their peers). First, the results showed that, in general, the relationships between values and well-being are weak to moderate, which is in line with other studies ( Vansteenkiste et al, 2006 ) and with a notion that values are related with eudaimonic rather than with hedonic well-being being studied here (see Joshanloo and Ghaedi, 2009 ; Bojanowska and Piotrowski, 2018 ). However, while it was true for adolescents from the general population, values had a significantly stronger impact on supervised teens’ satisfaction with life.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our first hypothesis stated that some values would be related to well-being but also that these links will be moderated by group (supervised vs. their peers). First, the results showed that, in general, the relationships between values and well-being are weak to moderate, which is in line with other studies ( Vansteenkiste et al, 2006 ) and with a notion that values are related with eudaimonic rather than with hedonic well-being being studied here (see Joshanloo and Ghaedi, 2009 ; Bojanowska and Piotrowski, 2018 ). However, while it was true for adolescents from the general population, values had a significantly stronger impact on supervised teens’ satisfaction with life.…”
Section: Discussionsupporting
confidence: 91%
“…A person for whom domination is a key element in their value hierarchy may be difficult in relationships, as cooperation would not be their default stance and they would rather focus on competition. This was confirmed in one study with reference to eudaimonic well-being (Bojanowska and Piotrowski, 2018). The function of humility, conformity, tradition, security, and face values for well-being is unclear.…”
Section: Basic Human Values and Well-beingmentioning
confidence: 87%
See 3 more Smart Citations